Diversity and relationship study of flora and avifauna in Babai river valley, Bardia Nepal - Kunwar, Ripu Mardan; Shakya, Suresh; Shrestha, Keshab (Journal of Natural History Museum, 2008)
Three distinct habitats: cultivated land, forest land and riverine land were observed. The dominant vegetation of forest lands, cultivated lands and riverine lands respectively were Shorea robusta and Terminalia alata; Ageratum conyziodes and Clerodendron viscosum; and Acacia catechu, Bombax ceiba and Dalbergia sissoo. A total of 284 plant species and 154 bird species were enumerated. Of total plant and bird species, five plant species and 14 bird species were found to be important in terms of relationship study between birds and plant communities. Habitat loss, deforestation, poaching and trapping, poisoning, grazing and timber smuggling were major threats and being major challenges for conservation of Babai river valley biodiversity. J. Nat. Hist. Mus. Vol.22, 2005 p.64-70